Conductometric and Spectrophotometric Studies of Thermodynamics of Complexation of Zn2+, Ni2+, Co2+, Pb2+ and Cu2+ Ions With 2,2’-Dimethyl-4,4’-bithiazole in Acetonitrile Solution - PAYEHGHADR, M.; ZAMANI, A. (Asian Journal of Chemistry, 2010)
In this work, the complexation reactions between 2,2'-dimethyl-4,4'- bithiazole (DMDTZ) and Zn2+, Ni2+, Co2+, Cd2+, Pb2+ and Cu2+ ions were studied conductometrically and spectrophotometrically in acetonitrile solution at various temperatures. The formation constants of the resulting 1:2 complexes were calculated from the computer fitting of the molar conductance-mole ratio data at different temperatures. At 25 ºC, the stability of the resulting complexes varied in the order Zn2+ > Ni2+ > Cu2+ > Co2+ > Cd2+ > Pb2+. The enthalpy and entropy changes of the complexation reactions were evaluated from the temperature dependence of formation constants.